Faktor – Faktor Pemicu Terjadinya Kesalahan Sistem Informasi Manajemen Terhadap Realisasi Penerimaan Puskesmas “X” - Faris Rahmawan; Tituk Diah Widajantie (Jurnal Informasi Pengabdian Masyarakat, 2023)
The management information system at the Puskesmas is the latest breakthrough in increasing the effectiveness of health services, and one of them   is   information   on   acceptance   at the Puskesmas. This study aims to reveal the triggers for the occurrence of management information system errors on the realization of acceptance at the Pukesmas "X". This research method uses a descriptive method, and this type of research is qualitative. The research subjects in this study were the employee staff at the Puskemas"X", while the object of this study was the Puskesmas management information system in the retribution reception section at the Puskemas"X". In the results of this study, it is known that the triggers for errors in the management information system for the realization of receipts are incorrect input, no verification, and double-checking before depositing, a system that often errors.